2015
DOI: 10.1002/smll.201402757
|View full text |Cite
|
Sign up to set email alerts
|

Plasmonic Ag@Oxide Nanoprisms for Enhanced Performance of Organic Solar Cells

Abstract: Localized surface plasmon resonance (LSPR), light scattering, and lowering the series resistance of noble metal nanoparticles (NPs) provide positive effect on the performance of photovoltaic device. However, the exciton recombination on the noble metal NPs accompanying above influences will deteriorate the performance of device. In this report, surface-modified Ag@oxide (TiO2 or SiO2 ) nanoprisms with 1-2 nm shell thickness are developed. The thin film composed of P3HT/Ag@oxides and P3HT:PCBM/Ag@oxides is inve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
41
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 54 publications
(43 citation statements)
references
References 39 publications
2
41
0
Order By: Relevance
“…Related studies have also shown that PL and light absorption by P3HT can be greatly enhanced by light scattering species. 65,66 Hence, the relatively high PL and UV-visible values for the P3HT-MG HTM ( Fig. 4c and d) and P3HT-MG film ( Fig.…”
Section: Perovskite Solar Cells Prepared Using Htm-mg Blendsmentioning
confidence: 94%
“…Related studies have also shown that PL and light absorption by P3HT can be greatly enhanced by light scattering species. 65,66 Hence, the relatively high PL and UV-visible values for the P3HT-MG HTM ( Fig. 4c and d) and P3HT-MG film ( Fig.…”
Section: Perovskite Solar Cells Prepared Using Htm-mg Blendsmentioning
confidence: 94%
“…The Ag@TiO 2 core-shell NPs were synthesized through an improvedm ethod of our previousr eports. [21,22] Transmission electron microscopy (TEM) image of Ag@TiO 2 NPs was shown in Figure1A. It presented core-shell structure in at riangle shape and TiO 2 was fully wrapped in the layer of Ag NPs.…”
Section: Ag@tio 2 Nanoprisms Characterizationsmentioning
confidence: 99%
“…The sol–gel route is another widely used method. Sun group has prepared Ag@TiO 2 core–shell nanoprisms using a mixture of citric acid and tetrabutyl titanite, affording a TiO 2 sol–gel precursor; this precursor was subsequently injected into the Ag nanoprism solution under vigorous stirring . The TiO 2 shell thickness was tuned via the control of the reaction time.…”
Section: Synthesis Of Various Shell‐isolated Nanoparticlesmentioning
confidence: 99%